2019
DOI: 10.35741/issn.0258-2724.54.6.36
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Air Pollution over Baghdad City Using Fixed Annual Stations and GIS Techniques

Abstract: Baghdad, considered one of the most polluted and populated cities in Iraq, waschoosen for mapping the distribution of air pollutants and the overall pollution levels by using the ArcGIS techniques. Six of main observation stations werechoosen in a particular location. Then, the recorded data from these stations were spatially interpolated using two types of ArcGIS interpolation techniques. The spatial interpolation techniques used in this work were Inverse distance weighting (IDW) and fuzzy logic. This study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…On the other hand, remote sensing data are considered low-cost data compared with data collected based on field investigations. With the development of spatial technology, many studies conducted depending on the GIS technique, Hasson et al, 2019 [35] used the spatial analysis technique (i.e. geo-statistical interpolation to represent the spatial distribution of the total column of carbon monoxide, and their results showed that Basra city and south of Baghdad are influenced by CO plumes either horizontally or vertically due to industrial activities.…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand, remote sensing data are considered low-cost data compared with data collected based on field investigations. With the development of spatial technology, many studies conducted depending on the GIS technique, Hasson et al, 2019 [35] used the spatial analysis technique (i.e. geo-statistical interpolation to represent the spatial distribution of the total column of carbon monoxide, and their results showed that Basra city and south of Baghdad are influenced by CO plumes either horizontally or vertically due to industrial activities.…”
Section: Related Workmentioning
confidence: 99%
“…The population of Baghdad governorate is about 10 million capita according to the 2019 census. Whole area of Baghdad province is estimated at 4555 square kilometers, while the area of Baghdad city is about 204.2 square kilometers [12]. Baghdad city is considered as an urban area with clear human activities, especially at city Centre, see figure 1.…”
Section: Locationmentioning
confidence: 99%
“…The concept of a smart city has been developed is a city that uses various technological methods to enhance operational efficiency, make services, control and management more aware, interactive and effective, share information with the public, and improve service quality. A smart city manages technologies such as transportation, health, education, energy, housing, buildings and the environment in a smart way [5] [6].…”
Section: Introductionmentioning
confidence: 99%